The challenge of implementing inclusive education for children with hearing impairment in Nigeria (2012)
This paper examined the concept of inclusive education, the characteristics of children with hearing impairment, benefits and the challenges of inclusive education. The authors identified some findings that highlighted the problems facing inclusive education in developing countries The paper finally focused on factors that could enhance the successful implementation of inclusive education especially in developing countries like Nigeria.